Integration of Tausug Literature in Filipino Course: The Case of Mindanao State University, Sulu - Alihuddin, Nadia A (Indonesian Community Empowerment Journal, 2021)
The non-integration of the Tausug literature in the school curriculum provides continuous degeneration of the Tausug literature in the minds and practices of the young Tausug. On the other hand, the integration of the Tausug literature in Filipino literature subjects will revive the dying culture of the Tausug. This study aimed to determine the components of the Tausug literature for integration into Filipino subjects. This study uses interpretative phenomenological analysis as its research design. Focus group discussion (FGD) was conducted to gain an in-depth understanding of social issues. Moreover, to obtain data from a purposively selected group, this FGD recruited four Tausug Filipino Professors and a Tausug Islamic studies Professor who lived in the province of Sulu as participants of the study. FGD was held in one classroom in the college of education for 2 hours, and open-ended questions were raised to elicit responses from the participants. The integration of the Tausug literature in Filipino subjects or in the educational curriculum is very relevant in the Muslim areas and in the promotion of quality education. Teaching and preserving cultural values and heritage are vital components of quality education. Therefore, this integration strengthened cultural preservation, which in turn led to increased student awareness. If the students became conscious of their cultural orientation, cultural practices became a uniting factor among the people in the community.